2015
DOI: 10.1108/mbe-11-2014-0045
|View full text |Cite
|
Sign up to set email alerts
|

Sustaining Sweden’s competitive position: lean lifelong learning

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 10 publications
1
19
0
Order By: Relevance
“…This condition is inverted with [17,51] which states that human resource is a dominant factor in building the learning society than marketing, place and capital. The results of the T test statistic in Table 4, signed that the conditions invalid batik craftsmen design characteristics (X2) against batik craftsmen performance (Y), showed Tcom < Tref (22,76 > 1,960), confirmed that the behavior of batik craftsmen utilizing design, gives influence to the formation batik craftsmen performance in the face of the competition era that in line with the research conducted by [26,56], in which the character designs in batik after have tended to show the results of batik as a work, deserving of appreciation from the other party. These conditions show that batik craftsmen has had motivation to make batik design as a profession, where the motivation to make batik design activities as a profession, according to data from observation field is 24%, and the need for the recognition of batik as a profession, based on the observations in field was 80%, so batik has actually had the awareness to make the character designs that have been owned to get recognition from the community of batik, consumers and governments , in order to face global competition.…”
Section: The Effect Of Batik Craftsmen Design Characteristics (X2)supporting
confidence: 78%
See 1 more Smart Citation
“…This condition is inverted with [17,51] which states that human resource is a dominant factor in building the learning society than marketing, place and capital. The results of the T test statistic in Table 4, signed that the conditions invalid batik craftsmen design characteristics (X2) against batik craftsmen performance (Y), showed Tcom < Tref (22,76 > 1,960), confirmed that the behavior of batik craftsmen utilizing design, gives influence to the formation batik craftsmen performance in the face of the competition era that in line with the research conducted by [26,56], in which the character designs in batik after have tended to show the results of batik as a work, deserving of appreciation from the other party. These conditions show that batik craftsmen has had motivation to make batik design as a profession, where the motivation to make batik design activities as a profession, according to data from observation field is 24%, and the need for the recognition of batik as a profession, based on the observations in field was 80%, so batik has actually had the awareness to make the character designs that have been owned to get recognition from the community of batik, consumers and governments , in order to face global competition.…”
Section: The Effect Of Batik Craftsmen Design Characteristics (X2)supporting
confidence: 78%
“…The definition of lifelong learning along with the development of the learning society, in its development led to the mastery of the knowledge to establish professionalism, in order to face the changes of the social environment and economics [2,[35][36]51]. Experts in the field of lifelong learning, by this time divided into two major groups namely (a) The expert on lifelong learning, which supports that lifelong learning is an attempt to master a certain competence on environmental change, as well as learning to live independently with a smart way including [26,44] and (b) the expert field of lifelong learning that is structured in an attempt to form a human being becomes a valuable investment, in the form of creations that are flexible and capable of being accepted in different environmental conditions of work including [2,23,40].…”
Section: Lifelong Learningmentioning
confidence: 99%
“…They are linked to the effectiveness of activities and performance of the whole organization or the learning organization. Hroník (2007) defines the concept of development using the concept of learning as "achieving the desired change by learning".…”
Section: Current State Of Knowledgementioning
confidence: 99%
“…Some authors investigated the impacts of further education on employees participating in this education (e.g. Isaksson, Garvare, Johnson, Kuttainen, & Pareigis, 2015;Khan, 2012). Other authors (e.g.…”
Section: Current State Of Knowledgementioning
confidence: 99%
“…On the other hand, UNESCO (2017) published the document: "Making sense of MOOCs; A Guide for Policy-Makers in Developing Countries", where it recognizes the great potential of MOOCs and promotes their development as a strategy in the frame of the plan "Education 2030: Quality and Inclusive Education". Likewise, Isaksson, Garvare, Johnson, Kuttainen, and Pareigis (2015) inform them as an alternative to a growing and unsatisfied demand of continuous education, despite their lack of acknowledgment to the official value of most of these (Law, 2015).…”
Section: Introductionmentioning
confidence: 99%